2018
DOI: 10.1177/1073274818775356
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Regarding HPV and Vaccination Among Chinese Women Aged 20 to 35 Years in Fujian Province

Abstract: The use of the human papillomavirus (HPV) vaccine was recently approved in Mainland China. This study determined the knowledge and attitudes of young women aged 20 to 35 years in Fujian Province, China, with regard to HPV and vaccination and explored the potential factors influencing their attitudes toward HPV vaccination. This was a cross-sectional study that collected data regarding the knowledge on and attitudes toward HPV and vaccination using questionnaires. Furthermore, the prevalence of HPV was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 37 publications
5
21
1
Order By: Relevance
“…A low introductory price for the vaccine may help in making the vaccine affordable and acceptable to Chinese women through government programmes. The associated factors affecting women's willingness to be vaccinated themselves which we detected in our study corroborate recent surveys of the same type [18,19,21,27]. Besides age, residency status, education level, marital status, income, HPV awareness, and specific knowledge of HPV and its vaccine, having daughter(s) is an important factor.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A low introductory price for the vaccine may help in making the vaccine affordable and acceptable to Chinese women through government programmes. The associated factors affecting women's willingness to be vaccinated themselves which we detected in our study corroborate recent surveys of the same type [18,19,21,27]. Besides age, residency status, education level, marital status, income, HPV awareness, and specific knowledge of HPV and its vaccine, having daughter(s) is an important factor.…”
Section: Discussionsupporting
confidence: 88%
“…The acceptability of HPV vaccination in our study was slightly higher than that reported in western China [19], whereas data from several multicentre or large-sample survey among the Chinese general female population suggest a higher acceptability(nearly or over 80%) [17,18,21]. The most common arguments against vaccination in our study included worries about the safety of the vaccine and considering HPV vaccination not being widely accepted, which both call for further education efforts.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Among the 1,376 participants involved in this survey, 1,240 participants (90.1%) representing 456 males (33.1%) and 784 females (57.0%) were aware of the terminology "cervical cancer." When stratified by gender, women had significantly greater knowledge, compared to men in terms of "cervical cancer being common in middle age (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) females" (75.5 vs. 67.5%, respectively, p ≤ 0.001). These participants were examined further to test their knowledge on some risk factors and symptoms of cervical cancer, as presented in Tables 2-4.…”
Section: Knowledge About Cervical Cancermentioning
confidence: 99%
“…However, most studies indicated that people by in large are in favour of using the vaccine 8 14 16 17. The positive attitude towards vaccination in some studies was observed to be driven by the fear of contracting HPV infection, cervical cancer and genital warts 18 19. Age and sexual activity were also noticed to be determining factors for parents agreeing to vaccinate their children 19.…”
Section: Introductionmentioning
confidence: 99%